2020
DOI: 10.1002/ajh.25951
|View full text |Cite
|
Sign up to set email alerts
|

Commercial anti‐CD19 CAR T cell therapy for patients with relapsed/refractory aggressive B cell lymphoma in a European center

Abstract: Two autologous anti-CD19 chimeric antigen receptors (CAR) T cells (axicabtagene ciloleucel [axi-cel] and tisagenlecleucel [tisa-cel]) are commercially approved in Europe for relapsed/refractory (R/R) diffuse large B cell lymphoma (DLBCL). We performed a retrospective study to evaluate patterns of use, efficacy and safety for axi-cel and tisa-cel. Data from 70 patients who underwent apheresis for commercial CAR T cells between January 2018 and November 2019 in our institution were retrospectively collected. Six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
99
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(115 citation statements)
references
References 25 publications
(67 reference statements)
14
99
1
1
Order By: Relevance
“…Different grading criteria for CRS may also contribute, as the Penn grading system results in higher number of grade 3–4 CRS in comparison to Lee system [ 144 , 145 ]. Real-world data confirmed results of the pivotal studies in general patient populations [ 146 ]. Analyses focused on older fragile patients and patients with CNS involvement reported safety and efficacy also in these clinical situations [ 147 , 148 ].…”
Section: Chimeric Antigen Receptor-based Adoptive Immunotherapysupporting
confidence: 75%
“…Different grading criteria for CRS may also contribute, as the Penn grading system results in higher number of grade 3–4 CRS in comparison to Lee system [ 144 , 145 ]. Real-world data confirmed results of the pivotal studies in general patient populations [ 146 ]. Analyses focused on older fragile patients and patients with CNS involvement reported safety and efficacy also in these clinical situations [ 147 , 148 ].…”
Section: Chimeric Antigen Receptor-based Adoptive Immunotherapysupporting
confidence: 75%
“…There is also promising data with targeted therapies, such as BET inhibitors. Finally, despite the low numbers in this category, the results presented on CAR‐T cells are very encouraging for DHL and THL 17‐20 …”
Section: Discussionmentioning
confidence: 88%
“…A total of four studies investigated the effects of glucocorticoids use on PFS (24)(25)(26)(27). Both Sesques et al and Nastoupil et al found no association between glucocorticoids use and PFS (24,27).…”
Section: Progression-free Survivalmentioning
confidence: 99%
“…A total of four studies investigated the effects of glucocorticoids use on PFS (24)(25)(26)(27). Both Sesques et al and Nastoupil et al found no association between glucocorticoids use and PFS (24,27). Holtzman et al also assessed the effects of duration (P = 0.32), total dose (P = 0.59), average daily dose and initial high-dose pulsing of glucocorticoids on PFS, however, no specific cut-off value was provided (26).…”
Section: Progression-free Survivalmentioning
confidence: 99%
See 1 more Smart Citation